(untitled) (International Journal of Advanced Research in Computer Science, 2017)
Grid computing technology is a technique to share various resources like memory, storage, processor that are idle, to solve very huge and complex problems. These resources are shared among various heterogeneous computers, which form a virtual organization. The computers involved in communication for sharing resources might be from the same domain or from different domains. The risk is more in communication among computers from different domains since they are unknown to each other and there are more chances to misuse the resources. To avoid the above mentioned problems, various trust models are prepared to assess the computers for their trustworthiness in communication. This paper proposes a trust model, which uses a regression model to predict the behavior of client and service provider for further communication in a more secure manner. This regression model is developed based on the data collected through a survey; also, a reliability test was conducted to check the consistency of collected data, which was found to be good. This paper also shows the usage of randomized algorithm for trust model in grid computing proposed by us, based on the various parameter values collected through the survey. Keywords: Grid Computing, Trust, Resource, Regression, Reliability.